“Gestión del talento humano y sus efectos en el desempeño laboral en la empresa Boho, Ambato” - Álvaro Bernardo, Cunalata Villar (2020)
The development of this research work was carried out in order to demonstrate how the management of human talent affects the job performance in the administrative and operational staff of the company BOHO, since in this time the company has not managed appropriate strategic guidelines for the various processes in the recruitment and recruitment of staff, which has been reflected in the poor performance of workers, as well as the progress of the company. This work details the situation of the company with respect to each of the factors immersed in the management of human talent, through critical knots identified in the approach to the problem in order to identify the impact on the administrative and operational workers. It is based through the state of the art with the background of other research, as well as the theoretical basis where it was addressed on the review of the company BOHO, clear guidelines of administrative management, as well as factors about performance Labour. This research made use of the descriptive method since it was based on the delimitation of a problem, followed by the construction of instruments for it, by observing the phenomena found, for a subsequent analysis of the information collected, in order to generate a diagnosis of environment, generating a proposal that in this case was the manual of procedures that mitigates the problem, in addition a non-experimental research design was used since there was no manipulation of any of the variables . The results of this research present conclusions and recommendations that will later serve as a reference axis for the company's executives.